2002
DOI: 10.1509/jimk.10.3.96.19543
|View full text |Cite
|
Sign up to set email alerts
|

Executive Insights: Building Successful Export Business Relationships: A Behavioral Perspective

Abstract: Although the United States has been one of the leading actors in international trade, limited evidence exists as to individual U.S. company relationships with overseas customers. On the basis of a sample of 201 U.S. exporting manufacturers, the authors draw a comparison between harmonious and problematic foreign business relationships. The findings reveal that, as opposed to problematic cases, firms with harmonious relationships are more experienced, employ more people, and exhibit more active behavior toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 16 publications
3
101
1
Order By: Relevance
“…Styles et al (2008) emphasize the model for relationship exchanges and its usefulness in understanding matters related to exporting, particularly the central constructs, namely: Trust and Commitment. Other studies have demonstrated a similar observation (Leonidou et al 2002, Ambler et al 1999. Given these findings, the present study seeks to answer the following question "How do trust and commitment affect small businesses and consequently increase their competitiveness and performance in export markets?…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Styles et al (2008) emphasize the model for relationship exchanges and its usefulness in understanding matters related to exporting, particularly the central constructs, namely: Trust and Commitment. Other studies have demonstrated a similar observation (Leonidou et al 2002, Ambler et al 1999. Given these findings, the present study seeks to answer the following question "How do trust and commitment affect small businesses and consequently increase their competitiveness and performance in export markets?…”
Section: Introductionmentioning
confidence: 54%
“…Nes et al (2007) contend that trust is the foundation of any business relationship, particularly when the relationship is sustained over the long term (Kumar et al 1995). Leonidou et al (2002) define trust as the belief of one party in a working relationship that the behavior of the other party is honest, sincere, and fair. Trust benefits exporters in terms of knowledge transfer and in counterbalancing the potential harmful effects of cultural differences.…”
Section: Effects Of Trust On Commitment Competitive Advantage and Ementioning
confidence: 99%
“…Cooperation stresses the joint efforts, team spirit and collaboration which is required from both exchange parties for achieving both inter-organizational and intraorganizational goals (Cannon & Perrault, 1997;Leonidou, Katsikeas & Hadjimarcou, 2002). Coordination involves the synchronization of activities and flows between parties and refers to situations in which parties work together to achieve mutual goals (Mohr & Nevin, 1990;Anderson & Narus, 1990).…”
Section: Inter-organizational Level (Western)mentioning
confidence: 99%
“…Researchers associated with the Industrial Marketing and Purchasing Group developed the interaction approach, which also emphasizes the importance of developing and maintaining a close and long-term relationship in a buyer-seller context (e.g. Håkansson, 1982;Leonidas, Katsikeas, & Hadjimarcou, 2002;Styles & Ambler, 1994). This study, which focuses on ongoing business relationships in an exporting context, is rooted in the theoretical perspectives claiming that longterm business relationships benefit the independent partners involved in the business relationship.…”
Section: Introductionmentioning
confidence: 99%